2016
DOI: 10.1002/jor.23392
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sensitivity to microstructure between cyclic- and impact-based microindentation of human cortical bone

Abstract: Unlike the known relationships between traditional mechanical properties and microstructural features of bone, the factors that influence the mechanical resistance of bone to cyclic reference point microindention (cRPI) and impact microindention (IMI) have yet to be identified. To determine whether cRPI and IMI properties depend on microstructure, we indented the tibia mid-shaft, the distal radius, and the proximal humerus from 10 elderly donors using the BioDent and OsteoProbe (neighboring sites). As the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
(46 reference statements)
0
8
2
Order By: Relevance
“…The determinants of BMSi are poorly understood, (23) though reports indicate that BMSi is negatively associated with intracortical porosity and positively associated with the ultimate bending stress of cortical bone, (24) factors which would be expected to also relate to fracture risk. Similar to prior reports we found a weak negative association between BMSi and age, (15) and a weak positive association between BMSi and aBMD by DXA.…”
Section: Discussionmentioning
confidence: 99%
“…The determinants of BMSi are poorly understood, (23) though reports indicate that BMSi is negatively associated with intracortical porosity and positively associated with the ultimate bending stress of cortical bone, (24) factors which would be expected to also relate to fracture risk. Similar to prior reports we found a weak negative association between BMSi and age, (15) and a weak positive association between BMSi and aBMD by DXA.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional microindentation was additionally used to test our specimens. This is an established method to investigate elastic deformation properties of bone at the microscale . Results indicated that ribose‐treated specimens had lower maximum force and stiffness, contributing to the observed 75% and 77% lower elastic modulus on the OLT and IR surfaces, respectively, compared with vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, IDI and BMSi correlated with tissue mineral density roughly to the same degree (r = −0.390; r = 0.430, respectively). Uppuganti et al have also found correlations between quasi-static apparent level mechanical behavior in bending to be correlated with BMSi 55 , while Abraham et al 33 did not 33 (Table 3). Yet whole bone mechanical behavior appears to be correlated with IDI 51 , and Granke et al 56 found moderate correlations between IDI and femoral cortical beam bending parameters.…”
Section: Studies Comparing Osteoprobe Biodent and Whole-bone Behaviormentioning
confidence: 92%
“…However, cadaver studies provide the opportunity to compare the BioDent and Osteoprobe with other mechanical testing modalities 33,54,55 . Karim and co-authors suggest BioDent measures creep or fatigue crack growth from cyclic loading, whereas OsteoProbe is sensitive to energy dissipated from rapid loading 54 .…”
Section: Studies Comparing Osteoprobe Biodent and Whole-bone Behaviormentioning
confidence: 99%
See 1 more Smart Citation